Sensitive determination of anatoxin-a, homoanatoxin-a and their degradation products by liquid chromatography with fluorimetric detection - James, Kevin J; Furey, Ambrose; Sherlock, Ian R; Stack, Mary A; Twohig, Marian; Caudwell, F.Barry; Skulberg, Olav M (Journal of Chromatography A, 1998)
Cyanobacterial neurotoxins have been implicated in animal deaths resulting from drinking contaminated water. Anatoxin-a (AN) and homoanatoxin-a (HMAN) have previously been analysed using high-performance liquid chromatography (HPLC) with UV detection, but this procedure is insufficiently sensitive and is subject to interferences. A sensitive fluorimetric (FL) method for determining AN was recently developed using derivatisation with 4-fluoro-7-nitro-2,1,3-benzoxadiazole (NBD-F) and this has been applied to the simultaneous determination of AN, HMAN and their epoxy and dihydro degradation products. Microscale syntheses were used to prepare the dihydro and epoxy derivatives from AN and HMAN. These compounds were produced in high yields, as confirmed by electrospray MS and HPLC–FL of their benzoxadiazole derivatives. All six NBD derivatives were readily separated using isocratic reversed-phase HPLC. The recoveries of these compounds from spiked water samples, using weak cation-exchange (WCX) solid-phase extraction (SPE), were 83.2–84.9% at concentrations of 10 μg/l. The R.S.D. values were 1.7–3.9% ( n=8) and the limits of detection were better than 10 ng/l for all six compounds, illustrating the high sensitivity of the method. This methodology was successfully applied to the analysis toxin degradation products in natural samples. Dihydroanatoxin-a (0.8 mg/g) was isolated from a benthic Oscillatoria bloom from Caragh Lake, Ireland, and was found to contain two isomers but their ratio was different from that found in the synthetic material.